Generation Z: För nit och redlighet i rikets tjänst : en kvalitativ studie om offentliga organisationers användande av Employer Branding för att rekrytera Generation Z - Lodén, Karl; Sederholm, Martin (SLU/Dept. of Economics, 2020)
About 1.4 million people work in the Swedish public sector. The public sector employs several different generations of employees and one of these generations is Generation Z (people born after 1995). According to OECD, several countries have been experiencing difficulties to recruit young workers into the public sector. It is considered that public organizations need to be better at designing their Employer Brand to be able to reach young workers. A model was developed by the authors to collect the data. The purpose of the study is to investigate how public organizations work with Employer Branding and how their marketed values are in line with Generation Z's values. A qualitative method has been used with an inductive approach. Five semi-structured interviews have been conducted with five different public organizations. The authors have adopted a thematic method of analysis to explain the themes and patterns in the data. By interviewing and studying different organizations, empirical data were gathered to answer the study's three research questions. Based on the findings, it can be concluded that all the organizations have developed strategies regarding their Employer Branding (EB). However, the degree of EB related work differs between the organizations. The organizations have distinct target audiences to which they adapt their EB. It is also evident that the communicated values of the organizations are highly valued by Generation Z. In conclusion, the public organizations appear to be prepared for adapting their EB to target Generation Z.